A Bioactive Synthetic Outer‐Core Oligosaccharide Derived from a Klebsiella pneumonia Lipopolysaccharide for Bacteria Recognition. Issue 25 (23rd March 2023) - Chen, Dushen; Srivastava, Akhilesh K.; Dubrochowska, Justyna; Liu, Lin; Li, Tiehai; Hoffmann, Joseph P.; Kolls, Jay K.; Boons, Geert‐Jan
Abstract: There is an urgent need for new treatment options for carbapenem‐resistant Klebsiella pneumoniae ( K. pneumoniae ), which is a common cause of life‐threatening hospital‐ and community‐acquired infections. Prophylactic or therapeutic vaccination may offer an approach to control these infections, however, none has yet been approved for human use. Here, we report the chemical synthesis of an outer core tetra‐ and pentasaccharide derived from the lipopolysaccharide of K. pneumoniae . The oligosaccharides were equipped with an aminopentyl linker, which facilitated conjugation to the carrier proteins CRM197 and BSA. Mice immunized with the glycoconjugate vaccine candidates elicited antibodies that recognized isolated LPS as well as various strains of K. pneumoniae . The successful preparation of the oligosaccharides relied on the selection of monosaccharide building blocks equipped with orthogonal hydroxyl and amino protecting groups. It allowed the differentiation of three types of amines of the target compounds and the installation of a crowded 4, 5‐branched Kdo moiety. Abstract : A chemical synthesised outer core tetra‐ and pentasaccharide derived from the lipopolysaccharide of K. pneumoniae conjugated to the carrier proteins CRM197 and BSA elicited in mice antibodies that recognized isolated LPS as well as various strains of K. pneumoniae demonstrating they can induce relevant antigenic responses.